THE IMPLICATION OF CHALMERS' ONTO-EPISTEMOLOGICAL PROPERTY DUALISM ON THE HARD PROBLEM OF CONSCIOUSNESS: A NEOSADRIAN PERSPECTIVE - Fadhlu Rahman; Alim Roswantoro; Kholid Al Walid; Hadi Kharisman (Sadra International Institute, 2024)
This study aims to examine the various onto-epistemological implications arising from Chalmers' property dualism within the framework of Neosadrian onto-epistemological substantialist dualism concerning consciousness. The methodology employed entails an onto-epistemological philosophical analysis, encompassing ontology and epistemology as the two branches of philosophy addressing the nature of reality and knowledge related to it. This onto-epistemological approach draws insights from various Neosadrian Islamic philosophical thinkers, including Taqi Misbah Yazdi, Muthahhari, Jawadi Amuli, and Thabataba’i. Consequently, the research inquiries encompass: firstly, elucidating how David J. Chalmers’ argument on property dualism addresses the conundrum of consciousness; and secondly, exploring how Neosadrian onto-epistemology scrutinizes the concepts and ramifications of Chalmers’ property dualism in relation to consciousness. The investigation demonstrates that Chalmers’ argumentation in response to the hard problem of consciousness refers to the principle of pan-physicalism, positing consciousness as the foundation of reality’s structure present in all entities. Moreover, consciousness, though distinct from matter, emerges from intricate material processes. Additionally, the unidirectional duality interaction (epiphenomenal) resulting from pan-physicalism, according to Chalmers, offers the most cogent explanation for bridging the onto-epistemological gap inherent in the hard problem of consciousness. From the Neosadrian perspective, Chalmers’ viewpoint carries implications: firstly, Chalmers’ pan-physicalism implies the absence of an ontological relationship between consciousness and matter, thereby perpetuating their entrapment in the ontological gap, which constitutes the central issue of the hard problem of consciousness. Secondly, as consciousness engenders something external to itself, it contradicts the principle of al-Wāḥid lā yaṣduru ‘anhu illā al-wāḥid in the Neosadrian perspective and elevates the position of structured reality (murakkab) over simple reality (basīṭ).